Tendon Functional Extracellular Matrix. Issue 6 (June 2015) - Screen, Hazel R. C.; Berk, David E.; Kadler, Karl E.; Ramirez, Francesco; Young, Marian F.
ABSTRACT This article is one of a series, summarizing views expressed at the Orthopaedic Research Society New Frontiers in Tendon Research Conference. This particular article reviews the three workshops held under the "Functional Extracellular Matrix" stream. The workshops focused on the roles of the tendon extracellular matrix, such as performing the mechanical functions of tendon, creating the local cell environment, and providing cellular cues. Tendon is a complex network of matrix and cells, and its biological functions are influenced by widely varying extrinsic and intrinsic factors such as age, nutrition, exercise levels, and biomechanics. Consequently, tendon adapts dynamically during development, aging, and injury. The workshop discussions identified research directions associated with understanding cell–matrix interactions to be of prime importance for developing novel strategies to target tendon healing or repair. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:793–799, 2015.